Preparation and Properties of Corrosion-Resistant Coatings From Waterborne Polyurethane Modified Epoxy Emulsion - Zhang, Jianjun; Huang, Hao; Ma, Jun; Huang, Luyao; Huang, Lu; Chen, Xiaohua; Zeng, Hao; Ma, Sude (Frontiers in Materials, 2019)
Corrosion of metal products can seriously affect their reliability. The application of coatings is the most widely used method of corrosion protection due to the desire of easy application and low cost. Most of the present corrosion resistant coatings are solvent coatings. Due to the high content of volatile organic compounds, the use of solvent coatings is restricted. Currently, the corrosion resistance of the waterborne coatings are much lower than that of the solvent coatings, so research and development of waterborne corrosion resistant coatings are necessary and valuable. The corrosion resistant waterborne polyurethane modified epoxy (WPUME) emulsion was prepared and characterized by the Fourier transformer infrared spectra, transmission electron microscopy and thermal gravimetric analysis. The particle size, dispersion, and the solid content of the emulsion were tested by the laser-scattering equipment and weighing method. Coatings were prepared based on the emulsion, and the properties (i.e. water absorption rate, salt spray resistance and flexibility) of the coatings were tested by the standard method, respectively. Results show that the synthesis reaction accords well with the molecular design, and the average diameter of the particles in the emulsion is 100 nm approximately. The cured coating have good flexibility and can withstand the salt spray test more than 60 days (i.e. 1440 hrs), which is coated on the tinplate sheets. The emulsion has many potential practical applications in the protection of the metal materials.